2018
DOI: 10.1108/ijpdlm-02-2017-0068
|View full text |Cite
|
Sign up to set email alerts
|

Resource commitment and sustainability: a reverse logistics performance process model

Abstract: Purpose The purpose of this paper is to extend existing and motivate future sustainable supply chain management (SCM) and logistics research by examining a structure-conduct-performance framework linking resource commitment to sustainable SCM, reverse logistics, and operational performance. A sustainable reverse logistics capability is investigated as mediating the performance benefits associated with resource commitments to sustainable SCM. Design/methodology/approach Survey methods and structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(127 citation statements)
references
References 76 publications
(80 reference statements)
2
121
0
1
Order By: Relevance
“…Allocation and supervision of financial resources is a praiseworthy act to support the poor community in sustainable and social practices. As pointed out by Morgan et al (2018), sustainable capability and practices are achieved through resource commitment and resources recycling effectively. Hence, organizations should efficiently use the resources in order to configure corporate social responsibility that benefits sustainable practices (Sueyoshi & Goto, 2019).…”
Section: Government Incentives Resources Management and Sdgsmentioning
confidence: 99%
“…Allocation and supervision of financial resources is a praiseworthy act to support the poor community in sustainable and social practices. As pointed out by Morgan et al (2018), sustainable capability and practices are achieved through resource commitment and resources recycling effectively. Hence, organizations should efficiently use the resources in order to configure corporate social responsibility that benefits sustainable practices (Sueyoshi & Goto, 2019).…”
Section: Government Incentives Resources Management and Sdgsmentioning
confidence: 99%
“…REL's significance is not related only to increasing profits, but also to better competing position, efficiency in performance, and customer satisfaction (YOGI, 2015;HUANG et al, 2015;EUCHI et al, 2019;AGRAWAL et al, 2016;GAMBOA;RIVEROS, 2019;SANGWAN, 2017;MAHINDROO et al, 2018;MORGAN et al, 2018).…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%
“…In 2015, the costs of reverse e-logistics' were about 130.6 billion USD and 223.6 billion USD for Asia-pacific and EMEA regions, respectively. Moreover, the returned products' costs for retailers recorded was about $260 billion for the same year (MORGAN et al, 2018). Returned products represent more than 35% of the total e-commerce retailers' cost (HUANG et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The results of a mediated model suggest by Morgan et al (2018) have indicated that resources commitment may be used to develop a sustainable reverse logistics capability and reduce the environmental impact of reverse logistics activities. This study suggests that firm resources committed to sustainable Supply Chain Management (SCM) through reverse logistics create structures within and across the supply chain.…”
Section: Relationship Between Reverse Logistics and Resources Commitmentmentioning
confidence: 99%